The effectiveness of semantic therapy for the word finding difficulties of children with severe and complex speech, language and communication needs. (February 2015) - Wilson, Jean; Aldersley, Anna; Dobson, Catherine; Edgar, Silke; Harding, Christian; Luckins, Jessie; Wiseman, Fiona; Pring, Tim
Word finding difficulties are often seen in children with language difficulties. Their problem is readily observed and has led to investigations of its nature and encouraged attempts at intervention. Semantic errors in their naming suggest that their knowledge of items is poorly developed and that therapies to strengthen it may be effective. Twelve children between 7 and 11 years of age were offered 3 hours of semantic therapy in two 15-minute sessions per week for 6 weeks. The children had severe and complex speech, language and communication needs and all were in the bottom 5% for their age on a test of word finding. Two categories of items were treated. Each category was divided into sets of items that were directly treated, and items which appeared during therapy but were not specifically targeted. Categories and sets of items were counterbalanced across children. The children were blind assessed on naming the items before and after therapy and at a maintenance assessment 6 weeks after the treatment ceased. The children improved significantly on the treated items and on untreated items from the same category but not on items from the untreated category. Improvement was maintained at the maintenance assessment. Although results were significant, only medium effect sizes were obtained. These results add to the evidence that semantic therapy can help children with word finding difficulties. In assessing their clinical significance, the severity of the children's communication problems should be taken into account.